2020
DOI: 10.3390/su122310152
|View full text |Cite
|
Sign up to set email alerts
|

Fishing with Pesticides Affects River Fisheries and Community Health in the Indio Maíz Biological Reserve, Nicaragua

Abstract: The practice of harvesting fish and crustaceans by using pesticides is understudied and under-reported in tropical inland fisheries yet poses a significant threat to freshwater biodiversity and community health. This research provides a brief review of the practice and an in-depth case study from southeast Nicaragua. In 2019, 86 interviews and 5 focus groups were conducted in remote communities in the Indio Maíz Biological Reserve (IMBR) and nearby surrounding area and combined with 4 years of local Indigenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Similar studies Olele et al [25] followed the same pattern on the composition, abundance and distribution of fishes in Onah Lake, Asaba, Nigeria, showed that site C was the most abundant with 1009 fish species followed by site A with 880 individuals and site B with the least abundance. The number of individuals in the present study, is far lower than that of the previous study Ikpi, [9] which has supports the possibility of a negative impact of anthropogenic activities, faulty agricultural practices leading to soil erosion and runoff of chemicals such as pesticides and fertilizers into the waterfalls, which is similar to the findings of Betts et al [4] that pesticides generally reduce the abundance and diversity of fish and aquatic invertebrates in rivers and streams that receive polluted runoffs [5] [6]. The present study is also higher than Ndome et al [26] on the ichthyofauna of the upstream and downstream reaches of the Kwa Falls, Oban, Cross River State, Nigeria with a total of 562 fish representing 12 species belonging to 11 genera from 10 families and 6 orders; and also higher [27] in the investigation of Otamiri River, with a total of 129 benthic fish fauna belonging to 5 species and 4 families with Chrysichthys nigrodigitatus (32.65%) as the most dominant fish species and Synodontis soloni (2.18%) as less dominant.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar studies Olele et al [25] followed the same pattern on the composition, abundance and distribution of fishes in Onah Lake, Asaba, Nigeria, showed that site C was the most abundant with 1009 fish species followed by site A with 880 individuals and site B with the least abundance. The number of individuals in the present study, is far lower than that of the previous study Ikpi, [9] which has supports the possibility of a negative impact of anthropogenic activities, faulty agricultural practices leading to soil erosion and runoff of chemicals such as pesticides and fertilizers into the waterfalls, which is similar to the findings of Betts et al [4] that pesticides generally reduce the abundance and diversity of fish and aquatic invertebrates in rivers and streams that receive polluted runoffs [5] [6]. The present study is also higher than Ndome et al [26] on the ichthyofauna of the upstream and downstream reaches of the Kwa Falls, Oban, Cross River State, Nigeria with a total of 562 fish representing 12 species belonging to 11 genera from 10 families and 6 orders; and also higher [27] in the investigation of Otamiri River, with a total of 129 benthic fish fauna belonging to 5 species and 4 families with Chrysichthys nigrodigitatus (32.65%) as the most dominant fish species and Synodontis soloni (2.18%) as less dominant.…”
Section: Discussionsupporting
confidence: 90%
“…The effects of these changes on aquatic systems are severe especially where there is increasing demand for freshwater resources generated by continued growth in human population, urbanization, industrialization, irrigation and agricultural development, which cause serious alterations of the aquatic communities [3]. For example, in aquatic systems, it is well known that pesticides generally reduce the abundance and diversity of fish [4] and aquatic invertebrates and cause changes in community composition in rivers that receive polluted runoff [5] [6]. In extreme cases, pesticide runoff from agriculture can result in large fish kills [7].…”
Section: Introductionmentioning
confidence: 99%
“…Organic substances like pesticides are harmful to fish, which can be said to reduce the health properties of fish meat [ 15 ]. According to Betts et al [ 16 ], the practice of using pesticides is a threat not only for inland fisheries, but it is a global problem, because as a consequence, it can be harmful for human health.…”
Section: Introductionmentioning
confidence: 99%
“…From the advent of colonialism to the present, Indigenous Peoples have a history of disempowerment in states that have asserted ownership of their traditional lands. Many Indigenous Peoples often have no legal ownership or tenure rights over their traditional lands and, for many of the countries where losses of forest have been greatest on IPL outside PAs, disenfranchisement has been strongly manifest in recent decades (e.g., Cameroon, Beckline et al., 2022; Bryan, 2019; Nicaragua, Betts et al., 2020). Even where IPL are managed by Indigenous Peoples with a conservation aim, governance and contextual factors, such as incentives for mining and access and use of IPL, might also lead to deforestation.…”
Section: Discussionmentioning
confidence: 99%